Pharmacological Activities of Citrus hystrix - Puji Kurniawati Rahman; Hamiseh; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Kaffir lime (Citrus hystrix) is a bushy, small and bushy plant which is mainly used for its fruit and leaves as a seasoning for cooking. Kaffir lime (Citrus hystrix) belongs to the Rutaceae family. Internationally, kaffir lime (Citrus hystrix) is known as